Detection of adenovirus antibody by counterimmunoelectrophoresis. - Petric, M (1979)
Counterimmunoelectrophoresis was adapted as a rapid, sensitive assay for detection of adenovirus group-specific antibody. This assay was six times more sensitive than the complement fixation test and was successfully adapted for use with microliter quantities of serum or whole blood.